PERANCANGAN E-CRM PADA PT ZERO CELCIUS INDONESIA - Tandjung, Ichwan Ridwan; Wijaya, Andy; Kesuma, Darwin; Bubun, Obed (CommIT (Communication and Information Technology) Journal, 2008)
Purpose of this research is to analyze and design an appropriate system to help PT. Zero CelciusIndonesia in offering service to their customers, in order to keep a good relationship and communication,and also to obtain information as needed. Research methods used were library study, customers’ needsanalysis, designing and creating of e-CRM system, programming, and system testing as suggested. Result gotfrom the survey to company was that the current CRM system was only run by limited company staffs.Whereas the clients owned by company were considered quite many. Therefore, a CRM based on web or alsoknown as e-CRM was being created. So, the conclusion is that because of e-CRM, a better service to thecustomers can be given more focus and a relationship between company and customers can be closer; notonly as market subjects, but as colleagues.